(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, by using the Krasnoselskii’s fixed-point theorem, we study the existence of positive periodic solutions of the following single-species model with delay weak kernel and cycle mortality: x'(t) = rx(t)[1 − 1K^t_−∞αe^ −α(t−s) x(s)ds] − a(t)x(t), and get the necessary conditions for the existence of positive periodic solutions. Finally, an example and numerical simulation are used to illustrate the validity of our results.